PENERAPAN MEDIA PUZZLE UNTUK PEMAHAMAN MATERI DAUR HIDUP HEWAN DI SEKOLAH DASAR DENGAN PENDEKATAN SAINS-EDUTAINMENT - Safrina Junita; Haris Munandar (Jurnal Tunas Bangsa, 2019)
This research was motivated by observations in several elementary schools in Aceh Besar and Banda Aceh that the fourth grade students of elementary school still had a low ability to describe and explain the steps in the life cycle of animals. In addition, the teacher also does not use the media in the learning process of animal life cycle concepts. The purpose of this study is to apply puzzle learning media to students' understanding of animal life cycle material. The results of the study indicate that the results of the application of media puzzles on the subject of animal life cycle can increase the understanding of fourth grade students of SD 69 on the material. This is evidenced by the acquisition of the value of student learning outcomes in the posttest with the percentage of 87.5% of students included in the category "Completed". While at pretest only 10.3% were declared "Completed". The results of the questionnaire showed that students' learning motivation towards the use of puzzle media was very high with the percentage of 89.4% of students stated motivated by the use of puzzle learning media. Abstrak Penelitian ini dilatarbelakangi oleh hasil observasi di beberapa sekolah dasar di Aceh Besar dan Banda Aceh bahwasanya siswa kelas IV SD masih memiliki kemampuan yang rendah dalam mendeskripsikan dan menjelaskan langkah-langkah daur hidup hewan. Selain itu, guru juga tidak menggunakan media dalam proses pembelajaran konsep daur hidup hewan. Tujuan penelitian ini adalah menerapkan media pembelajaran puzzle untuk pemahaman siswa terhadap materi daur hidup hewan. Hasil penelitian menunjukkan bahwa hasil penerapan media puzzle pada pokok bahasan daur hidup hewan dapat meningkatkan pemahaman siswa kelas IV SD 69 terhadap materi tersebut. Hal ini dibuktikan dengan perolehan nilai hasil belajar siswapadaposttest denganpersentase 87,5% siswatermasukdalamkatagori ”Tuntas”. Sedangkan pada pretest hanya 10,3% yang dinyatakan “Tuntas”.Hasil angket menunjukkan bahwa motivasi belajar siswa terhadap penggunaan media puzzle sangat tinggi dengan persentase 89,4% siswa menyatakan termotivasi dengan penggunaan media pembelajaran puzzle. Kata Kunci: Media Pembelajaran, Daur Hidup Hewan, Puzzle